Desain Pisau Pengurai dan Sistem Pengayak serta Uji Produk Mesin Pengolah Sabut Kelapa sebagai Bahan Mentah Komposit - Roy Aries Permana Tarigan; Kaleb Priyanto; Jenal Sodikin; M R Pratama; I R Ramadhani (Infotekmesin, 2024)
This research aims to design a decomposing blade, sieving system, and test machine products. The method for completing coconut fiber processing machines consists of three stages, namely the design and production process stages, as well as machine product testing. This research produces the following data, namely the design of the untangling knife which is a combination of the functions of the coir untangling knife for random and woven results. Calculation of the equilibrium moment on the shaft obtained a value of ???????????? is 28.68 N and the reaction at point A was ???????????? is 28.32 N, with the diameter of the shaft used in the coconut fiber sieving machine transmission system being Ø28 mm. Fiber uniformity is obtained from twice decomposition processes, whereas the level of fiber/powder uniformity is influenced by the long sieving process time and also the high rotational speed of the sieve.